Acetohydroxy acid synthase I, a required enzyme for isoleucine and valine biosynthesis in Escherichia coli K-12 during growth on acetate as the sole carbon source. - Dailey, F E (1986)
Escherichia coli K-12 has two acetohydroxy acid synthase (AHAS) isozymes (AHAS I and AHAS III). Both of these isozymes catalyze the synthesis of alpha-aceto-alpha-hydroxybutyrate and alpha-acetolactate, which are key intermediates of the isoleucine-valine biosynthetic pathway. Strains lacking either isozyme but not both activities have been previously shown to grow well in minimal media in the absence of isoleucine and valine on any of several commonly used carbon sources (e.g., glucose or succinate). We report the characterization of mutants that were unable to grow on either acetate or oleate as a sole carbon source due to a defect in isoleucine-valine biosynthesis. The defect in isoleucine-valine biosynthesis was expressed only on these carbon sources and was due to the loss of AHAS I activity, resulting from lesions in the ilvBN operon. Previously identified ilvBN mutant strains also failed to grow on acetate or oleate minimal media. Our results indicated that AHAS I is an essential enzyme for isoleucine and valine biosynthesis when E. coli K-12 is grown on acetate or oleate as the sole carbon source. AHAS III was expressed during growth on acetate or oleate but was somehow unable to produce sufficient amounts of alpha-aceto-alpha-hydroxybutyrate and alpha-acetolactate to allow growth.